Perdagangan Sukuk SR020 di Pasar Modal Indonesia dalam Perspektif Sosiologi dan Antropologi - Arman Rajiman; Tajul Arifin; Dedah Jubaedah (CV. Kalimasada Group, 2025)
Sukuk Sukuk has become an important Islamic financial instrument in Indonesia, in line with the government's commitment to strengthening the sharia economy and meeting massive development financing needs. It is crucial to examine how the public responds to sharia financial products like Sukuk, particularly from sociological and anthropological perspectives, to understand how social, cultural, and religious factors influence investment decisions. This study uses a literature review method, combining the findings of similar studies from various scientific sources. Descriptive analysis through this literature review is used to verify previous studies and identify new contributions. The sales of Retail Sukuk SR020 reached Rp21.359 trillion from 63,009 investors. This widespread interest demonstrates society's adaptation, including that of the millennial generation, to sharia investment principles. Sociological data shows cross-gender and cross-generational participation, with millennials dominating the number of investors, while Generation X dominates the order volume7. Anthropologically, this interest illustrates how religious and social norms influence financial decisions. The trading of Sukuk SR020 reflects the social and cultural dynamics of society, as well as a mindset shift from merely saving to investing. This instrument not only serves as an investment tool but also as a reflection of religious and cultural values.